Natural spring water gargle samples as an alternative to nasopharyngeal swabs for SARS‐CoV‐2 detection using a laboratory‐developed test. Issue 3 (3rd November 2021) - Gobeille Paré, Sarah; Bestman‐Smith, Julie; Fafard, Judith; Doualla‐Bell, Florence; Jacob‐Wagner, Mariève; Lavallée, Christian; Charest, Hugues; Beauchemin, Stéphanie; Coutlée, François; Dumaresq, Jeannot; Busque, Lambert; St‐Hilaire, Manon; et al.
Abstract: The objective of this study was to validate the use of spring water gargle (SWG) as an alternative to oral and nasopharyngeal swab (ONPS) for SARS‐CoV‐2 detection with a laboratory‐developed test. Healthcare workers and adults from the general population, presenting to one of two COVID‐19 screening clinics in Montréal and Québec City, were prospectively recruited to provide a gargle sample in addition to the standard ONPS. The paired specimens were analyzed using thermal lysis followed by a laboratory‐developed nucleic acid amplification test (LD‐NAAT) to detect SARS‐CoV‐2, and comparative performance analysis was performed. An individual was considered infected if a positive result was obtained on either sample. A total of 1297 adult participants were recruited. Invalid results ( n = 18) were excluded from the analysis. SARS‐CoV‐2 was detected in 144/1279 (11.3%) participants: 126 from both samples, 15 only from ONPS, and 3 only from SWG. Overall, the sensitivity was 97.9% (95% CI: 93.7–99.3) for ONPS and 89.6% (95% CI: 83.4–93.6; p = 0.005) for SWG. The mean ONPS cycle threshold (Ct ) value was significantly lower for the concordant paired samples as compared to discordant ones (22.9 vs. 32.1; p < 0.001). In conclusion, using an LD‐NAAT with thermal lysis, SWG is a less sensitive sampling method than the ONPS. However, the higher acceptability of SWG might enable a higher rate of detection from a population‐based perspective. Nonetheless, in patients with a high clinical suspicion of COVID‐19, a repeated analysis with ONPS should be considered. The sensitivity of SWG using NAAT preceded by chemical extraction should be evaluated. Highlights: Using a laboratory‐developed NAAT preceded by thermal lysis, the overall percent agreement between spring water gargle (SWG) and oral combined with nasopharyngeal swab (ONPS), sampled at the same time among 1297 participants, is excellent (98.6%). Although the SARS‐CoV‐2 NAAT from SWG is globally less sensitive than from ONPS (89.6% vs. 97.9%), the difference is markedly less in individuals symptomatic for <3 days (2.7%; p=NS) than in those whose symptoms started ≥7 days before testing (35.7%; p = 0.005).